Herbivory in the soft coral Sinularia flexibilis (Alcyoniidae) - Piccinetti, Chiara C; Ricci, Roberta; Pennesi, Chiara; Radaelli, Giuseppe; Totti, Cecilia; Norici, Alessandra; Giordano, Mario; Olivotto, Ike (Scientific reports, 2016)
Our work provides strong support for the hypothesis that Sinularia flexibilis ingests diatoms such as Thalassiosira pseudonana. We assessed algal ingestion by S. flexibilis through estimates of algal removal, histological analyses, scanning electron microscopy observations, and gene expression determination (18S and silicon transporter 1) by real time PCR. Cell counts are strongly suggestive of algal removal by the coral; light and scanning microscopy provide qualitative evidence for the ingestion of T. pseudonana by S. flexibilis, while molecular markers did not prove to be sufficiently selective/specific to give clear results. We thus propose that previous instances of inability of corals to ingest algae are reconsidered using different technical approach, before concluding that coral herbivory is not a general feature.
Keywords: Anthozoa; Herbivory; Animals; stravovací zvyklosti; býložravci; Plankton; plankton; zvířata; korálnatci; Diatoms; dieta; Diet; DNA; Feeding Behavior; rozsivky